No death, no fear : comforting wisdom for life - Hanh,Thich. Nhat. (London : Sydney : Rider, 2002)
'(Thich Nhat Hanh) shows us the connection between personal, inner peace and peace on earth' His Holiness the Dalai LamaThich Nhat Hanh says: 'Our biggest fear is that we will become nothing when we die.
Keywords: Spiritual life -- Buddhism; Buddhism -- Doctrines; Fear of death